Compounds and commands in the evolution of human language - Progovac, Ljiljana (Theoria et Historia Scientiarum, 2012)
My conclusion is that the grammar behind VN compounds is the best candidate for a living fossil of proto-syntax. Little about these compounds makes sense except in the light of evolution. Their rudimentary flat combinatorial strategy, defying the most fundamental principles of modern morpho-syntax (e.g. headedness) is accompanied by the semantics and use that point to ritual insult and sexual selection, specializing for derogatory reference. Adding to the exotic nature of VN compounds, their verb surfaces in a(n) (proto-) imperative form. If VN compounds started to be coined in the ancient oneword stage of human language, a stage characterized by the use of imperative verb forms, it is to be expected that they would have been tinkered from what was already available, the imperative forms. These crude compounds, typically exhibiting the most basic of vocabulary, can nonetheless express abstract (human) traits not only with astounding succinctness, but also with humor and playfulness. Using this kind of compounding strategy at the dawn of language would have not only augmented the expressive power of human language enormously, but it would have also provided a foundation for future vocabulary and structure building.